KEANEKARAGAMAN SPESIES TUMBUHAN PADA PARAK AGROFORESTRI PARAK DI NAGARI BUKIK LIMBUKU KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT - Merry Syafrida; Defri Yoza; M. Mardhiansyah M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
ABSTRACTThe objective of the research is to know the composition and diversity level at Parak forestry, as now a days Parak decreases in number of growth so it must be developed by agroforestry, Nagari Bukik Limbuk is a place that conducts its kind of development. The technique of sampling is systematic sampling with random start. The result of the research showed the level of diversity at Parak Cocoa is 3.05 by the number of sampel about 1556 and total number is 52 species, if it vigure out per level, trees, saplings, seedlings and understorey it has the number of level at the middle, than low level for the pole. Parak Cocoa used random pattern and durian also avocado becomes the share for cocoa, cocoa found 77 numbers. Parak corn has the level of diversity at the middle, 2.48. The highest number at the seedling and understorey is 2.37, it is also mid level. then at the level of trees and poles classified as middle, and at the level of saplings classified as low. The pattern used is fence pattern, the plants for the fence are coconut, cacao and avocado. The number of plants at Parak Jagung is 1367 and the highest number is corn about 450. The both of Parak combined agrosilvopastura by the discovery of fish pool at the Parak cocoa, and also goat and cow at the Parak corn. Keyword: Diversity, Agroforestry, Parak, Vegetation Analysis